Bahasa Inggris - Setyawan, Heri (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
This study explores Said Nursi’s thoughts on interreligious dialogue as articulated in his monumental work, Risale-i Nur, within the socio-political context of Turkey in the 1920s, a period marked by the transition from the Ottoman Caliphate to the secular Republic. Amid tensions between Western modernization and Islamic tradition, Nursi developed a theological and socio-political thoughts that underscored the necessity of interreligious dialogue for the sake of peace, moral integrity, and mutual progress. In particular, The Words and The Letters, sections within Risale-I Nur, reveal Nursi’s understanding that interreligious dialogue arises from a faith-based commitment to truth, compassion, and justice. Nursi argues that ethical solidarity among the Abrahamic faiths, Islam, Christianity, and Judaism, constitutes a share responsibility before humanity and God. Exploration on interreligious dialogue within historical contexts of Turkey, provides an important contribution to finding a model of interfaith dialogue that resists secularist assumptions and remains profoundly relevant to the pursuit of religious harmony in today’s pluralistic world. الملخص تتناول هذه الورقة البحثية أفكار سعيد النورسي حول الحوار بين الأديان، كما عبّر عنها في عمله الرائد